SATU DASAWARSA RELASI POLITIK LOKAL DAN NASIONAL DALAM KONTEKS OTONOMI DAERAH - KISNO HADI, KISNO HADI (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractThis paper will describe relationship between local and national politics in regional autonomycontext in recent ten years which is ruling by Governor as representative of National Government inlocal region and Regent/Mayor as implementer of regional autonomy. Analytical tools for this paper isUU No.22/1999 about Local Government and its revision in UU No. 32/2004 and some of PeraturanPemerintah which are following of both regulations. Focus of this paper are (1) Roles and functions ofLocal Government Province and Governor as an actor of decentralization, deconcentration andmedebewind; (2) Roles and functions Governor as representative of National Government in LocalRegion; and (3) Political impact of relationship disharmony between Governor – as representative ofNational Government in Local Region – and Regent/Mayor as implementer of regional autonomy. Atlast, I give same recommendation for strengthening position, role and authority for Governor asrepresentative National government in local region.Keywords : political relationship, national and local, role and function, political impact, authority.